Development of Spanish requests and apologies during study abroad - Shively, Rachel L.; Cohen, Andrew D. (Íkala, Revista de Lenguaje y Cultura, 2008)
The present study analyzed the requests and apologies of 67 U.S. American study abroad students before and after spending one semester in a Spanish-speaking country. Ratings of students' pragmatic appropriateness by Spanish native speakers indicated that, overall, students improved their request and apology performance over the course of the semester. An analysis of students' request and apology strategy use, both pre- and post-study abroad, found that in certain ways students shifted their behavior to more closely resemble that of Spanish native-speaker baseline data, but that in some cases, they also remained or moved away from native-speaker norms. Another objective of the study was to examine the possible associations between students' background characteristics, contact with Spanish, and gains in intercultural sensitivity with gains over time in rated request and apology performance. Of these variables, only two of the language contact variables yielded statistically significant results. This study contributes to our understanding of second language pragmatic development and the influence of individual characteristics and environmental factors. Recibido: 14-12-2007 / Aceptado: 07-08-2008 How to reference this article: Shively, R. L. & Cohen, A. D. (2008). Development of Spanish requests and apologies during study abroad. Íkala. 13(2), pp.57-118.